Implementation of SAK-EMKM and Accounting Information Technology on Quality of Financial Report - Digita, Archie; Sulistiawati, Clara (Journal of Business and Economics Research (JBE), 2025)
This research aims to determine the effect of implementing SAK-EMKM and the use of accounting information technology on the quality of financial reports. The method used in this research is a purposive method, some criteria need to be met, namely, the Coffee Shop is classified as an MSME and not a coffee shop. The sample that met the criteria was 130 Coffee Shops. Data collection was carried out using a questionnaire, the data of which was then tested using validity and reliability tests. This research has shown that the result of SAK-EMKM shows a strong and beneficial influence concerning the standard of financial statements. It is proven by the t value of 12.159 with a significance value of 0.000, which means it is smaller than 0.05 (0.000<0.05) and Accounting Information Technology has a positive and strong influence on the standard of financial statements. This is proven by the t value of 9.310 with a significance value of 0.000, which means it is smaller than 0.05 (0.000<0.05).